Designing a Productive Waqf Strategy Based on Plasma Waqf to Accelerate Sustainable Development in Cirebon - Muhaimin, Muhaimin; Nur Maarif, Muhamat (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2026)
This study aims to design a strategic implementation of productive waqf through a plasma waqf scheme to support sustainable development in Cirebon Regency. Waqf management is still dominated by traditional models that are not aligned with human development. Waqf has not yet been able to reduce poverty and suffering. This study employs a qualitative case study approach; data were collected through in-depth interviews, observations, and documentation involving key stakeholders, including waqf managers, the Cirebon Regency government, and beneficiaries. The research findings indicate that the design for productive waqf development utilizes the plasma waqf scheme through a dual-track investment approach: the development of micro-enterprise units and business projects developed by government financial institutions. Waqf institutions and the government conduct regular joint oversight to ensure success. To strengthen human resources, all business unit managers are trained in skills and management through a group-based concept where members mutually evaluate one another. Evaluation and monitoring are conducted in an integrated manner among the government, the waqf trustees (nadzir), and the business units as implementers. This scheme represents a new model where waqf management undergoes a shift in coordination and managerial transformation. This scheme aligns with the path toward achieving the SDGs to eradicate poverty and strengthen humanity.